2018
DOI: 10.1016/j.marpolbul.2017.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Comparing methods suitable for monitoring marine mammals in low visibility conditions during seismic surveys

Abstract: Loud sound emitted during offshore industrial activities can impact marine mammals. Regulations typically prescribe marine mammal monitoring before and/or during these activities to implement mitigation measures that minimise potential acoustic impacts. Using seismic surveys under low visibility conditions as a case study, we review which monitoring methods are suitable and compare their relative strengths and weaknesses. Passive acoustic monitoring has been implemented as either a complementary or alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 36 publications
0
30
0
1
Order By: Relevance
“…Because whales would produce both weak and strong blows over time, the decrease in perceptibility of weak blows (though still .50%, Fig. 4a) at distances greater than 3 km, is not overly concerning in a mitigation context especially because mitigation and monitoring zones generally have radii ,3 km (Verfuss et al 2016). Perceptibility was shown not to be influenced by relative humidity (Fig.…”
Section: A Thermal Perceptibilitymentioning
confidence: 92%
See 2 more Smart Citations
“…Because whales would produce both weak and strong blows over time, the decrease in perceptibility of weak blows (though still .50%, Fig. 4a) at distances greater than 3 km, is not overly concerning in a mitigation context especially because mitigation and monitoring zones generally have radii ,3 km (Verfuss et al 2016). Perceptibility was shown not to be influenced by relative humidity (Fig.…”
Section: A Thermal Perceptibilitymentioning
confidence: 92%
“…It has previously been shown that fog has a significant impact on the transmission of longwave infrared (LWIR) radiation due to an increase in Mie scattering with large fog droplets (Verfuss et al 2018). Unfortunately, the impact fog has on the ability of the system to detect whales is impossible to measure within the thermal perceptibility protocol as human observers are also strongly impacted by fog.…”
Section: ) Fogmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, and sometimes even within waters of the same country (e.g. the United States), no single minimum standard of mitigation measures exists (Verfuss et al 2018). In countries where mitigation measures are recommended, the standards are often guidelines rather than requirements (Compton et al 2007, Parsons et al 2009, Nowacek et al 2015.…”
Section: Knowledge Gaps Surrounding Mitigation Measuresmentioning
confidence: 99%
“…Dedicated marine mammal observers (MMO) or protected species observers (PSOs) can monitor zones prior to and during operations to provide real-time information (ACCOBAMS 2013; NOAA 2016). Additionally, passive acoustic monitoring systems can be used to detect the presence of vocally active species around exclusion zones, especially when visual observations by MMOs are impaired (i.e., during night and inclement weather, or due to submerged animals; Verfuss et al 2018). If organisms are observed inside exclusion zones, operations are halted until the organisms have vacated the zone (NOAA 2016).…”
Section: Exclusion Zonesmentioning
confidence: 99%